Research higlights formulation of high performance, multipurpose grease using gypsum from titanium dioxide manufacturing waste - Abdulbari, Hayder A. (Penerbit UMP, 2009)
1. GREASES • The use of liquid lubricant generally requires sealing of bearing against loss of lubricants.